Manajemen Fisioterapi Pada Pasien Yang Terkena Cedera ACL Pasca Operasi: Literatur Review - Amar Nur Ichsan; Dini Nur Alpiah (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Anterior Cruciate Ligament (ACL) injury is one of the most common injuries, particularly among athletes, often requiring ACL reconstruction surgery to restore optimal knee function. Postoperative ACL rehabilitation necessitates a comprehensive physiotherapy approach to prevent complications such as pain, edema, reduced range of motion (ROM), and to improve muscle strength and joint stability. Various physiotherapy modalities have been widely used during rehabilitation, but further evaluation of their effectiveness is still required. This study aims to evaluate the physiotherapy management of patients following ACL reconstruction, focusing on therapeutic modalities used to reduce pain, improve ROM, strengthen muscles, and prevent complications, as well as to assess the outcomes of various physiotherapy interventions. This literature review gathers data from five articles published between 2020 and 2024, which discuss various physiotherapy interventions for patients post-ACL reconstruction. These articles include the use of ultrasound, electrotherapy (TENS), patellar mobilization, eccentric quadriceps exercise, and manual therapy. The data collected covers results such as pain reduction, ROM improvement, edema reduction, and muscle strength enhancement. The findings of this review indicate that ultrasound therapy and eccentric quadriceps exercises are effective in reducing pain and improving tendon flexibility, while patellar mobilization and electrotherapy (TENS) are shown to be effective in reducing edema and improving knee ROM. Additionally, muscle strength and dynamic balance also improved with structured strengthening exercises. The comprehensive application of these therapeutic modalities accelerates recovery in patients after ACL reconstruction surgery, although some patients may still require additional time to reach full athletic capacity